PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PADA BADAN USAHA MILIK NEGARA (BUMN) - Istighfarin, Diana; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2015)
Recently, many companies have been realizing the importance of Good Corporate Governance (GCG) and is believed that it effect significantly the profit of companies. This study aimed to examine the effect of corporate governance on the profitability of the BUMN. Proxy of GCG, namely: institutional ownership, the size of the independent board, audit committee and corporate governance perception index (CGPI), the profitability of BUMN in proxy with the ratio of net profit margin (NPM). The research sample was determined by purposive sampling technique, and there are 30 sample observations that qualify as research samples. Data analysis technique used is multiple linear regression. The results show that institutional ownership and CGPI significant positive effect on profitability, while the size of the independent board and audit committee does not have a significant effect on profitability.
Keywords: good corporate governance, profitability